2022
DOI: 10.3390/jintelligence10040077
|View full text |Cite
|
Sign up to set email alerts
|

Developing Children’s Creativity and Social-Emotional Competencies through Play: Summary of Twenty Years of Findings of the Evidence-Based Interventions “Game Program”

Abstract: This work presents the results of four cooperative-creative game programs (Game Programs). In all four studies, experimental designs with repeated pretest-posttest measures and control groups were used. Validation samples ranged from 86 to 178 participants, randomly assigning participants to the experimental and control conditions. Before and after each program, a battery of assessment instruments was applied to measure the variables under study. The intervention consists of conducting a weekly game session du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
9
0
2
Order By: Relevance
“…Despite these limitations, the study has important practical implications for school health professionals The results suggest the importance of implementing at school programs to promote self-esteem particularly, along with other factors of socioemotional development (e.g., prosocial behavior, assertive communication, empathy, etc. ), due to its efficacy in decreasing violence and anti-cyberbullying programs that also stimulate transversally socioemotional development factors [ 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, the study has important practical implications for school health professionals The results suggest the importance of implementing at school programs to promote self-esteem particularly, along with other factors of socioemotional development (e.g., prosocial behavior, assertive communication, empathy, etc. ), due to its efficacy in decreasing violence and anti-cyberbullying programs that also stimulate transversally socioemotional development factors [ 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…youth in our study spoke of ‘love’, ‘family’ and ‘home’; see also Lunga et al., 2022). The effect of guided play on SEL programming has been explicitly explored by few studies of youth development programming, only in relation to collaborative/co‐operative games (Garaigordobil et al., 2022; Hromek & Roffey, 2009). By exploring playfulness more broadly—an array of games and playful activities/approaches (Pyle et al., 2017)—these findings point to new ways of conceptualizing social development programming, contributing to filling the gap in PYD research about ‘light‐handed interventions’ (Lopez & McKnight, 2002), process over content (Roffey, 2017) and ‘being’ over ‘doing’ (Shek et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They can experiment with various materials and techniques to discover their unique way of expressing themselves, and this sense of control can help children develop the conviction that they can conquer new obstacles and achieve their goals. Another study by Garaigordobil et al (2022) indicated that creative play can assist children in developing problem-solving skills. When youngsters are engaged in creative play, they figure out how to overcome obstacles.…”
Section: Creative Play Activitiesmentioning
confidence: 99%
“…Creative play, on the other hand, can assist youngsters in building self-efficacy (Garaigordobil et al, 2022;Hunter et al, 2014). Self-efficacy is the belief that one can complete a task successfully.…”
Section: Creative Play Activitiesmentioning
confidence: 99%